Tick fauna of Baluran Wildlife Reserve, Indonesia - Munaf Basri Hasan (Hemera Zoa, 1978)
Thirteen species of ticks, both ixodids and argasids, from Baluran Wildlife Reserve., Indonesia, were collected between 1960 and 1975 from different hosts as well as from vegetation. Records of each species are provided with additional notes on its distribution, hosts association and other remarks relative to its occurence in Indonesia.